Ubiquitous computing in children education: framework for georeferenced multisensory information - Pedro Moreira da Silva (2009)
The traditional teaching methods, although very important, fail to explore the potential of interactive group collaboration and multisensory communication. Research has consistently shown that interactive and collaborative group learning, compared to traditional methods, produce greater learning and individual achievement. Learning can be fun, but for that, students need to be on scene and not just spectators. This paper presents a framework that handles the creation of georeferenced multisensory information, placing the content creation control in the hands of junior explorers the children. Mobile sensors spread across the exploring area, provide georeferenced environment information such as air temperature and humidity. Using multimedia (video, image, sound and text) teachers can bring the outside world into their classroom and share it with other classrooms across the globe. Having schools budgets in mind, when using this framework only content exploration using Google Earth requires Internet connection, that is, content creation can be made anywhere without any costs.